Corn Silk Tea: Artificial Chemical Free - Ab Razak, Siti Noraiza; Nur Zuhaili Amrang; Nur Atikah Halid; Nurshuhadah Mohd Ayob (Multidisciplinary Applied Research and Innovation, 2023)
Corn silk tea commonly used to treat infections of the urinary and genital system, such as cystitis, prostatitis and urethritis. The additional of stevia leaves into organic chemical free product give beneficial effect on blood glucose and insulin levels in human bodies because of its natural and sweet-tasting calorie free botanical. The production of an organic tea produced from dried corn silk with stevia leaves is the main goal of the study. The active compounds of both corn silk and stevia leaves are determine by using Fourier-Transform Infrared spectroscopy FTIR. From the analysis, the potential hydrogen of corn silk tea was 7.54 and it contains beneficial chemical compounds that is good for health. Through this research, it is expected to produce tasty yet healthy herbal tea, as well as to develop awareness to public about the advantages on consuming the corn silk tea.